An updated meta-analysis of the relationship between vitamin D levels and precocious puberty - Cheng, Hong; Chen, Dan; Gao, Hui (Frontiers in Endocrinology, 2023)
Background Some studies have investigated the association between vitamin D levels and precocious puberty (PP) but with limited sample sizes and inconsistent conclusions across studies. Methods Until July 2022, a comprehensive electronic search of works of literature was conducted in MEDLINE, Web of Science, and CNKI (Chinese National Knowledge Infrastructure). A systematic review and meta-analysis of 15 case-control studies with 2145 cases and 2063 controls was conducted to explore the relationship between vitamin D and PP. Stratified analyses by year of publication, country, diagnosis category of PP, child’s sex, and methods of 25(OH)D test were conducted. Results There was a negative correlation between 25(OH)D concentrations and PP in all study populations (SMD = -1.046, 95%CI = -1.366, -0.726). The pooled SMD remained significant in Chinese studies (SMD = -1.113, 95%CI = -0.486, -0.741), studies published before or after 2018 (SMD = -0.9832 and -1.185, 95%CI = -2.044, -1.133 and -1.755, -0.726), studies with female children (SMD = -1.114, 95%CI = -1.446, -0.781), and studies using electrochemiluminescence to detect 25(OH)D (SMD = -0.999, 95%CI = -1.467, -0.531). Vitamin D deficiency also increased the risk of PP (OR = 1.531, 95%CI = 1.098, 2.134). Unfortunately, heterogeneity was high in all analyses, and there was some publication bias. Conclusion This systematic review and meta-analysis demonstrated an association between vitamin D and precocious puberty. We recommend more high-quality studies, especially prospective cohort studies with big sample sizes or some randomized controlled intervention trials, to validate the reliability of the results.